The Role of Administrative Engineering in Supporting Administrative Innovation (Comprehensive Journal of Science, 2026)
This study aimed to identify the role of administrative engineering in supporting administrative innovation through the following dimensions: examining the role of administrative engineering in supporting administrative innovation within organizations; assessing the level of application of administrative engineering principles in existing administrative systems and processes; identifying the impact of administrative engineering on developing organizational structures and improving the work environment in a way that enhances administrative innovation; and identifying the obstacles that limit the effectiveness of administrative engineering in supporting administrative innovation within organizations.The descriptive approach was adopted due to its suitability for the purposes of the study. The study reached the following results:The study confirmed that administrative engineering contributes effectively to supporting administrative innovation through the redesign of processes and organizational structures.It was found that the level of application of administrative engineering principles in existing administrative systems and processes varies among organizations depending on their ability to adopt modern methods, the extent of employee training, the availability of human and technological resources, and the leadership’s capacity to manage change effectively.The study showed that administrative engineering has a positive impact on the development of organizational structures and the improvement of the work environment.The study also confirmed the existence of obstacles that limit the effectiveness of administrative engineering in supporting administrative innovation, most notably resistance to change, traditional organizational culture, lack of skills and competencies, financial and technological constraints, and weak strategic planning. This highlights the need for integrated strategies to overcome these obstacles and achieve sustainable impact.
Keywords: Administrative Engineering; Administrative Innovation